Sustainable waste management behavior in Malaysian higher education institutions: Integrating TPB and VBN perspectives for social development - Amran, Azzah; Ab. Aziz, Nasuhar; Mohd Shafie, Siti Nurhafizah; A. Malek @ Abdul Malek, Syazwani; Abdul Rahman, Rahayu; Mohamed, Zulkifli (Journal of Islamic, Social, Economics and Development, 2026)
This study examines sustainable waste management behavior within Malaysian higher education institutions by integrating the Theory of Planned Behavior (TPB) and Value-Belief-Norm (VBN) theory. Using a quantitative approach, data from 378 respondents were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that subjective norms and perceived behavioral control significantly influence sustainable waste practices, while financial incentives exhibit selective moderating effects. Beyond behavioral prediction, the study contributes to the discourse on social and institutional development by emphasizing the role of collective responsibility, environmental ethics, and value-driven engagement among university communities. The findings offer practical implications for policy makers and educational administrators in designing sustainability programs that strengthen social awareness, governance mechanisms, and long-term environmental accountability in higher education settings.